2013
DOI: 10.1002/hed.23241
|View full text |Cite
|
Sign up to set email alerts
|

Novel tandem germline RET proto‐oncogene mutations in a patient with multiple endocrine neoplasia type 2B: Report of a case and a literature review of tandem RET mutations with in silico analysis

Abstract: We describe a novel combination of tandem RET mutations (Q781R/V804M) in a MEN2B-like patient. In silico analysis showed a high prediction score, which was compatible with the clinical phenotype in the present case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…Немногочисленные сообщения о двойных мутациях противоречивы в отношении по-тенциирующего влияния второй мутации на клини-ческие проявления, в том числе на возраст манифе-стации наследственного МРЩЖ и синдрома МЭ-Н2А [8,9,[11][12][13]. В ряде работ [6,9,13,[18][19][20][21][22][23] со-общается о более агрессивном течении МРЩЖ, более высокой пенетрантности феохромоцитомы, появлении ганглионейроматоза, характерного для синдрома МЭН2Б, эктопической продукции АКТГ опухолью (МРЩЖ или феохромоцитомой) у боль-ных с множественными RET мутациями. Поэтому, хотя в данном случае роль каждой мутации в отдель-ности позволяла придерживаться тактики активно-го наблюдения, наличие одновременно двух мута-ций послужило аргументом в пользу профилактиче-ской тиреоидэктомии.…”
Section: Discussionunclassified
“…Немногочисленные сообщения о двойных мутациях противоречивы в отношении по-тенциирующего влияния второй мутации на клини-ческие проявления, в том числе на возраст манифе-стации наследственного МРЩЖ и синдрома МЭ-Н2А [8,9,[11][12][13]. В ряде работ [6,9,13,[18][19][20][21][22][23] со-общается о более агрессивном течении МРЩЖ, более высокой пенетрантности феохромоцитомы, появлении ганглионейроматоза, характерного для синдрома МЭН2Б, эктопической продукции АКТГ опухолью (МРЩЖ или феохромоцитомой) у боль-ных с множественными RET мутациями. Поэтому, хотя в данном случае роль каждой мутации в отдель-ности позволяла придерживаться тактики активно-го наблюдения, наличие одновременно двух мута-ций послужило аргументом в пользу профилактиче-ской тиреоидэктомии.…”
Section: Discussionunclassified
“…Following our report, 11 types of double mutations, including ours, were reported in patients with MEN 2 syndromes (table 1) [4,5,6,7,8,9,10,11,12]. The phenotypes in these cases were FMTC in 2 cases, MEN 2A in 4 cases, and MEN 2B in 5 cases.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that these 2 missense mutations were on the same allele in a tandem fashion, that Y806C was inherited from the patient's father and V804M was a de novo mutation, and that the transforming activity of RET with the V804M/Y806C mutations was moderately high [2,3]. Following our report, several other cases of double mutations of RET were reported in a small number of patients with MEN 2 [2,4,5,6,7,8,9,10,11,12]. Here we report that the same tandem mutations were inherited to our former patient's daughter, causing the MEN 2B phenotype and thus confirming the results of the in vitro studies as a natural experiment.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the underlying risk is that the less-common double or multiple RET mutations may be missed. Tandem germline RET mutations have been identified in patients with atypical forms of MEN2B (involving codons V804M and Y806C, S904C, E805K or Q781R) and based on in silico algorithms, their transforming ability was high correlating with a more aggressive clinical course [3,4]. Multiple RET mutations have also been found in kindreds with familial MTC, a variant of MEN2A [5].…”
mentioning
confidence: 99%